Barriers and facilitators to HIV and viral hepatitis testing in primary healthcare settings in the Kyrgyz Republic: A mixed-methods study using the COM-B Framework - Ida Sperle; Nikolay Lunchenkov; Anastassiya Stepanovich-Falke; Zuridin S. Nurmatov; Aybek A. Bekbolotov; Aisuluu Bolotbaeva; Aman Taalaibekov; Zamira Abdrakhmanova; Zulpueva Akmaral Aidarbekovna; Michael Brandl; Olena Kysil; Stela Bivol; et al. (PLoS ONE, 2025)
Introduction The Kyrgyz programme on the elimination of HIV and ending AIDS and viral hepatitis infections (2023–2027) recognizes the need to scale up testing and include primary healthcare. Our aim was to identify and analyse important barriers and facilitators to HIV and hepatitis B, C and D testing from the perspective of medical doctors working in primary healthcare in the Kyrgyz Republic. Methods We conducted a cross-sectional, mixed-methods study in the Kyrgyz Republic from June to November 2024, and first conducted in-depth semi-structured interviews. We applied a thematic analysis for qualitative analysis. We developed a questionnaire based on these main themes, which was distributed to medical doctors working in primary healthcare. A descriptive analysis of the questionnaire data followed. Results Through 21 interviews, we identified training gaps, lack of knowledge, lack of time and physical space as well as social and cultural perceptions as key barriers. Data from 1,080 questionnaire responses (89% female; 46% 61 years or older) supported this with 35% reporting lack of time, 39% lack of doctors, and over 60% indicating need for further training. Identified facilitators included knowledge of guidelines, new technologies, e.g., self-testing, and the possibility of linking testing to hepatitis B vaccination. Questionnaire data confirmed access to free testing and treatment (HIV: 86%, viral hepatitis 89%), knowledge of testing indications (HIV: 80%, viral hepatitis: 76%), and linkage to vaccination (71%) as important facilitators. Lack of experience with key populations was evident with 78% not identifying any members of key populations as patients. Conclusion To increase testing and reach the goals of ending AIDS and the epidemics of viral hepatitis, doctors in primary healthcare need capacity-building in the form of HIV and viral hepatitis training and knowledge dissemination to offer testing. Moreover, the availability and distribution of doctors in primary healthcare need to be prioritized and enhanced in areas in most need of care to ensure access to testing for all in the Kyrgyz Republic.